Financial Analysis of Egg-Laying Chicken Business, MSME Program, Animal Husbandry Study Program, Flores Bajawa Agricultural College - Marten Umbu Kaleka; Maria Alfonsa Ngaku; Egidius Rembo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The livestock sector plays a crucial role in the Indonesian economy, both in determining total national output and creating jobs. The egg-laying chicken business is one of the businesses in the livestock sector that offers significant and promising opportunities and is currently being widely developed. This study aims to analyze the financial sustainability of the MSME Program in the Animal Husbandry Study Program at the Flores Bajawa Agricultural College. The method used in this study is a case study. This method is used to fully explore the program's impact, financial success, and benefits obtained from the program. Data techniques used are in-depth interviews and literature studies, so the data used are primary and secondary data. Based on the research results and discussion above, it can be concluded that the MSME Program in the Animal Husbandry Study Program provides students with increased experience and competency in developing entrepreneurial knowledge and skills in the livestock business. From a financial aspect, the egg-laying chicken business shows positive value and is worth continuing because it provides financial benefits for both the institution and the study program, especially supporting the sustainability of the MSME program itself. Using a 12% discount rate, the NPV is greater than 1 for IDR 4,358,165.02, while the Net B/C is greater than 1.10, and the IRR is greater than 12%.